Effects of general, specific and combined warm-up on explosive muscular performance - David Cristobal Andrade; Carlos Henriquez-Olguin; Ana Rosa Beltran; Marco Antonio Ramirez; Cristian Labarca; Marcelo Cornejo; Cristian Alvarez; Rodrigo Ramirez-Campillo (Termedia Publishing House, 2015)
The purpose of this study was to compare the acute effects of general, specific and combined warm-up (WU) on explosive performance. Healthy male (n=10) subjects participated in six WU protocols in a crossover randomized study design. Protocols were: passive rest (PR; 15 min of passive rest), running (Run; 5 min of running at 70% of maximum heart rate), stretching (STR; 5 min of static stretching exercise), jumping [Jump; 5 min of jumping exercises - 3x8 countermovement jumps (CMJ) and 3x8 drop jumps from 60 cm (DJ60)], and combined (COM; protocols Run + STR + Jump combined). Immediately before and after each WU, subjects were assessed for explosive concentric-only (i.e. squat jump - SJ), slow stretch-shortening cycle (i.e. CMJ), fast stretch-shortening cycle (i.e. DJ60) and contact time (CT) muscle performance. PR significantly reduced SJ performance (p =0.007). Run increased SJ (p =0.0001) and CMJ (p =0.002). STR increased CMJ (p =0.048). Specific WU (i.e. Jump) increased SJ (p =0.001), CMJ (p =0.028) and DJ60 (p =0.006) performance. COM increased CMJ performance (p =0.006). Jump was superior in SJ performance vs. PR (p =0.001). Jump reduced (p =0.03) CT in DJ60. In conclusion, general, specific and combined WU increase slow stretch-shortening cycle (SSC) muscle performance, but only specific WU increases fast SSC muscle performance. Therefore, to increase fast SSC performance, specific fast SSC muscle actions must be included during the WU.